Kualitas Pelayanan dan Kemampuan Pengurus Sebagai Upaya Peningkatan Partisipasi Anggota pada Koperasi Sehati PKK RT 02 RW 07 Kelurahan Margahayu Utara Kecamatan Babakan Ciparay Kota Bandung - Manzilatusifa, Uus; Juliantoro, Samuel Rudie; Pertiwi, Mentari Puteri (Jurnal Pengabdian Tri Bhakti, 2022)
Community Service Program entitled "Service Quality and Management Capability as an Effort to Increase Member Participation in the Cooperative Sehati PKK RT 02 RW 07 North Margahayu Village, Babakan Ciparay District, Bandung City". There are 51 members of the cooperative. This activity is a follow-up to previous service activities, namely Efforts to Improve the Quality of Financial Reporting in the calculation of SHU. Therefore, our Devotion Team will provide assistance regarding the services and capabilities of the management as an effort to increase member participation. Participation of members in the services of produced by the cooperative will exist if there are three paths or/three roads and the suitability between members' requests for their needs, programs, and management decisions (administrator) means that the management must be able to make decisions in making programs in order to fulfill member requests in accordance with the needs set must be served by the cooperative. This identity criterion is important because from the system it can be shown that the owners and customers of an organization are identical individuals so that they have a greater opportunity to meet their needs through services in each cooperative activity.